Review on Biological Characteristics of Kv1.3 and Its Role in Liver Diseases - Liu, Junda; Lv, Xiong-Wen; Zhang, Lei; Wang, Hua; Li, Jun; Wu, Baoming (Frontiers in Pharmacology, 2021)
The liver bears the biggest proportion of macrophages among all solid organs in the body. Liver macrophages are mainly composed of cytolytic cells inherent in the liver and mononuclear macrophages recruited from the blood. Monocytes recruitment occurs mainly in the context of liver injury and inflammation and can be recruited into the liver and achieve KC-like phenotype. During the immune response of the liver, macrophages /KC cells release inflammatory cytokines and infiltrate into the liver, which are considered to be the common mechanism of various liver diseases in the early stage. Meanwhile, macrophages /KC cells form an interaction network with other liver cells, which can affect the occurrence and progression of liver diseases. From the perspective of liver disease treatment, knowing the full spectrum of macrophage activation, the underlying molecular mechanisms, and their implication in either promoting liver disease progression or repairing injured liver tissue is highly relevant from a therapeutic point of view. Kv1.3 is a subtype of voltage-dependent potassium channel, whose function is closely related to the regulation of immune cell function. At present, there are few studies on the relationship between Kv1.3 and liver diseases, and the application of its blockers as a potential treatment for liver diseases has not been reported. This manuscript reviewed the physiological characteristics of Kv1.3, the relationship between Kv1.3 and cell proliferation, apoptosis, and the role of Kv1.3 in a variety of liver diseases, so as to provide new ideas and strategies for the prevention and treatment of liver diseases. In short, by understanding the role of Kv1.3 in regulating the functions of immune cells such as macrophages, selective blockers of Kv1.3 or compounds with similar functions can be applied to alleviate the progress of liver diseases and provide new ideas for the prevention and treatment of liver diseases.